Creedal meanings and Islamic Manners in Duaa - Al Helwa, Haifa Bent Ahmed Bin Abdullah (Arab Journal for Sciences and Research Publishing, 2018)
All praise is due to Allah, and may peace and blessings be upon our Prophet Muhammad and upon his family and Companions. This Research is titled "Creedal meanings and Islamic Manners in Duaa". It is about the most important creedal meanings and Islamic manners in Duaa and it is based on the books of our Muslim Scholars. My research starts with an introduction where I mentioned the importance of the subject and why I chose it, the previous studies, the research outline and the research method. The Preface contains definitions of some of the Research terms. The first chapter of my research is about the legality and merits of Duaa, and the second is about the creedal meanings in Duaa. The third chapter is about lowering our voices during Duaa, and the forth is about its creedal meanings. The fifth chapter is about raising our hands during Duaa, and the sixth is about its creedal meanings. The seventh chapter is about believing in Allah to answer our Duaa, and the eighth is about its creedal meanings. I ended the research with a conclusion about the main findings and recommendations.